Analisis Utilitas Biaya Dalam Mendukung Pengambilan Keputusan Pada Sistem Jaminan Kesehatan - Ellin Rachmawati; Indah Laily Hilmi; Triana Maudy Yulianti Surasa; Dytha Andri Deswati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Health insurance systems face growing challenges in determining which interventions should be financed under limited resources, making it necessary to adopt approaches that can assess both health benefits and economic consequences simultaneously. One widely used approach is cost-utility analysis, which relates intervention costs to utility-based outcomes, particularly quality-adjusted life years (QALYs). This review article aimed to examine the role of cost-utility analysis in supporting decision-making within health insurance systems. This study was conducted as a review article through a systematic literature search in the PubMed database using the keyword “cost-utility analysis” AND “decision making”. The article selection process followed the PRISMA framework. Of the 131 records initially identified, 10 articles met the inclusion criteria after screening titles/abstracts (n=116 excluded) and full-text review (n=5 excluded), and were analyzed using a descriptive narrative approach. The review found that cost-utility analysis has been applied to assess various interventions, including palliative care services, antiviral therapies, artificial intelligence-based screening technologies, chronic disease medications, and national immunization programs. Several interventions were found to be cost-effective or even cost-saving, suggesting their potential to support benefit package expansion and improve the efficiency of health financing. However, other interventions were not considered economically feasible due to high prices, substantial budget impact, and limited reimbursement mechanisms. All reviewed studies originated from Thailand, Tiongkok, Vietnam, Colombia, Jepang, Korea Selatan, dan, Taiwan, Province of China; therefore, direct generalization to the Indonesian context requires further adaptation assessment. These findings indicate that cost-utility analysis plays an important role in informing benefit package design, health technology adoption, price negotiation, and more efficient resource allocation in health insurance systems. Therefore, the integration of cost-utility evidence into health financing policy should be strengthened to ensure that health insurance systems operate in a more rational, efficient, and sustainable manner.